2006
DOI: 10.1523/jneurosci.4493-05.2006
|View full text |Cite
|
Sign up to set email alerts
|

GABAergic Signaling at Mossy Fiber Synapses in Neonatal Rat Hippocampus

Abstract: In the adult rat hippocampus, granule cell mossy fibers (MFs) form excitatory glutamatergic synapses with CA3 principal cells and local inhibitory interneurons. However, evidence has been provided that, in young animals and after seizures, the same fibers can release in addition to glutamate GABA. Here we show that, during the first postnatal week, stimulation of granule cells in the dentate gyrus gave rise to monosynaptic GABA A -mediated responses in principal cells and in interneurons. These synapses were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
139
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(156 citation statements)
references
References 61 publications
16
139
1
Order By: Relevance
“…Previous studies have suggested that DG granule cells express GABAergic phenotypes (Walker et al, 2001;Gutiérrez, 2003;Safiulina et al, 2006), which are gradually decreased with development, and eventually disappear at around P24, and the time course of the change in GABAergic phenotypes is similar to that of the fiber volley facilitation discovered in the present study (Figs. 3,4 F).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have suggested that DG granule cells express GABAergic phenotypes (Walker et al, 2001;Gutiérrez, 2003;Safiulina et al, 2006), which are gradually decreased with development, and eventually disappear at around P24, and the time course of the change in GABAergic phenotypes is similar to that of the fiber volley facilitation discovered in the present study (Figs. 3,4 F).…”
Section: Discussionsupporting
confidence: 89%
“…Previous studies have shown that the granule cells in the DG express GABAergic phenotypes (Gutiérrez, 2003), and glutamate and GABA are coreleased from the mossy fiber terminal during the first 3 weeks after birth (Walker et al, 2001;Safiulina et al, 2006). Thus, the source of GABA responsible for the fiber volley facilitation may be not only GABAergic interneurons but also the mossy fiber terminal itself.…”
Section: Gabaergic Interneurons Contribute To the Fiber Volley Facilimentioning
confidence: 99%
“…Dual glutamate/GABA transmission at MF synapses is supported by the following evidence: (1) GAD and VIAAT are expressed in MFTs (Sloviter et al, 1996;Gutiérrez et al, 2003;Zander et al, 2010), (2) GABA is released from isolated MF synaptosomes (Gó mez-Lira et al, 2002), (3) GABAA receptors are expressed in the postsynaptic density facing GAD-immunopositive MFTs (Bergersen et al, 2003), and (4) IPSCs are detected upon extracellular stimulation in st. granulosum (Walker et al, 2001;Gutiérrez et al, 2003;Safiulina et al, 2006; but see Mori et al, 2004;Uchigashima et al, 2007;Toni et al, 2008). Our results appear consistent with some of these observations but do not support the conclusion that postsynaptic GABAA receptors are activated by GABA release at MFTs upon phasic activity.…”
Section: Discussioncontrasting
confidence: 69%
“…1), together with the presence of local interneurons in the granule cell layer and hilus (Lübke et al, 1998;Houser, 2007) complicates the interpretation of postsynaptic responses evoked by extracellular electrical stimulation (Walker et al, 2001;Safiulina et al, 2006;Uchigashima et al, 2007). We examined the postsynaptic responses evoked by photostimulation of individual, visually identified GCs using local photolysis of MNI-glutamate in hippocampal organotypic slices from G42 mice.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation